(untitled) (The Batuk, 2023)
The purpose of the study was to understand and analyze the strength of corporate governance (CG) on organizational performance (OP) of the Nepalese telecom industry from the employees’ perspective. It adhered to a descriptive study approach and employed an organized questionnaire survey instrument. Two market-leading telecommunication service provider companies of Nepal, Ncell and Nepal Telecom, and their employees were considered the object of the study. It collected 387 responses through a random sampling method. The survey instrument included 18 items and was divided into three segments to collect required data that was processed with the help of SPSS and AMOS software. The study identified nine observable CG performance metrics inside two latent variables, management and leadership (ML) and management competency (MC), to evaluate CG performance and revealed that each performance metric offers a partial explanation for the synergistic effects on OP. The study’s findings provided evidence to previous studies that CG performance positively and significantly affects the OP. In addition, the results of the study would deliver useful suggestions for comprehending the primary drivers of CG performance metrics in the Nepalese context.